Impacts of Protective Structures on Sandy Beaches: Example of the Saly Balnear Station, Petite Côte, Senegal - Ngom, Habib; Ndour, Abdoulaye; Niang, Isabelle (Journal of coastal research, 2018)
Ngom, H.; Ndour, A., and Niang, I., 2018. Impacts of protective structures on sandy beaches: Example of the Saly balnear station, Petite Côte, Senegal. In: Almar, R.; Almeida, L.P.; Trung Viet, N., and Sall, M. (eds.), Tropical Coastal and Estuarine Dynamics. Journal ofCoastal Research, Special Issue No. 81, pp. 114–121. Coconut Creek (Florida), ISSN 0749-0208. Several protective structures have been built in recent years to protect sandy beaches of the seaside resort of Saly threatened by erosion processes. However, the protective seawalls, groynes and breakwaters have not produced the expected results. Erosion processes continue on the sandy coast of Saly. The shoreline evolution was estimated by two methods: a study of the evolution of the shoreline between 1989 and 2016 by the DSAS and a monthly monitoring in 2014 of a series of 8 beach profiles. The results show a considerable sedimentary imbalance between a northwestern sector generally in accumulation and a southeastern sector under erosion separated by the groyne of the Safary residence. The combination of different protective structures inhibits the manifestation of positive effects of some of them. In the southeastern sector, breakwaters slightly reduce the erosion rates of the beach which are still affected by the return flows associated with the groynes of northwestern sector. Riprap walls occupy recreational beaches and are subject to scour and submersion that make them unstable. All beaches just upstream of the groynes are generally in accretion. Beaches protected by newly constructed groynes are experiencing a remarkable accretion. All this shows that groynes are much more favorable than the breakwaters or seawalls for accretion on the sandy coast of Saly. A well-sized and structured groynes field that takes into account the physical and climatic characteristics of the coast could in the long term stabilize the sandy beaches of Saly.